Posttraumatic Stress Symptoms Among Chinese College Students During the COVID-19 Pandemic: A Longitudinal Study - Xinli Chi; Liuyue Huang; Daniel L. Hall; Daniel L. Hall; Raissa Li; Kaixin Liang; Md Mahbub Hossain; Tianyou Guo (Frontiers Media S.A., 2021)
A longitudinal assessment of the prevalence of posttraumatic stress symptoms (PTSS) and risk factors is indispensable for further prevention and/or treatment. The longitudinal web-based survey enrolled 1,164 college students in China. Measured at two time points (February and August 2020), PTSS, demographic information, adverse childhood experiences (ACEs), resilience and self-compassion information were collected to explicate the prevalence and predictors of PTSS concurrently and over time. Results showed that although PTSS generally declined throughout the 6 months after the outbreak of COVID-19, the prevalence remained relatively high. Resilience and self-compassion negatively predicted PTSS concurrently and longitudinally. While subjective family socioeconomic status (SES) and ACEs at Wave 1 did not predict PTSS under COVID-19 at Wave 1, but both significantly predicted PTSS at Wave 2. Findings implicate potential targets for detecting and intervening on symptoms of trauma in this vulnerable population.